Catheter Ablation for Atrial Fibrillation in Adult Congenital Heart Disease: An International Multicenter Registry Study. (8th September 2022) - Griffiths, Jack R.; Nussinovitch, Udi; Liang, Jackson J.; Sims, Richard; Yoneda, Zachary T.; Bernstein, Hannah M.; Viswanathan, Mohan N.; Khairy, Paul; Srivatsa, Uma N.; Frankel, David S.; Marchlinski, Francis E.; Sandhu, Amneet; et al.
Abstract : Background: Data on atrial fibrillation (AF) ablation and outcomes are limited in patients with congenital heart disease (CHD). We aimed to investigate the characteristics of patients with CHD presenting for AF ablation and their outcomes. Methods: A multicenter, retrospective analysis was performed of patients with CHD undergoing AF ablation between 2004 and 2020 at 13 participating centers. The severity of CHD was classified using 2014 Pediatric and Congenital Electrophysiology Society/Heart Rhythm Society guidelines. Clinical data were collected. One-year complete procedural success was defined as freedom from atrial tachycardia or AF in the absence of antiarrhythmic drugs or including previously failed antiarrhythmic drugs (partial success). Results: Of 240 patients, 127 (53.4%) had persistent AF, 62.5% were male, and mean age was 55.2±13.3 years. CHD complexity categories included 147 (61.3%) simple, 68 (28.3%) intermediate, and 25 (10.4%) severe. The most common CHD type was atrial septal defect (n=78). More complex CHD conditions included transposition of the great arteries (n=14), anomalous pulmonary veins (n=13), tetralogy of Fallot (n=8), cor triatriatum (n=7), single ventricle physiology (n=2), among others. The majority (71.3%) of patients had trialed at least one antiarrhythmic drug. Forty-six patients (22.1%) had reduced systemic ventricular ejection fraction <50%, and mean left atrial diameter was 44.1±8.2 mm. Pulmonary vein isolation was performed in 227 patients (94.6%); additional ablation included left atrial linear ablations (40%), complex fractionated atrial electrogram (19.2%), and cavotricuspid isthmus ablation (40.8%). One-year complete and partial success rates were 45.0% and 20.5%, respectively, with no significant difference in the rate of complete success between complexity groups. Overall, 38 patients (15.8%) required more than one ablation procedure. There were 3 (1.3%) major and 13 (5.4%) minor procedural complications. Conclusions: AF ablation in CHD was safe and resulted in AF control in a majority of patients, regardless of complexity. Future work should address the most appropriate ablation targets in this challenging population.